2019
DOI: 10.1111/jth.14391
|View full text |Cite
|
Sign up to set email alerts
|

Loss of fibrinogen in zebrafish results in an asymptomatic embryonic hemostatic defect and synthetic lethality with thrombocytopenia

Abstract: Loss of fibrinogen in zebrafish has been previously shown to result in adult onset hemorrhage Hemostatic defects were discovered in early fga−/− embryos but well tolerated until adulthood Afibrinogenemia and thrombocytopenia results in synthetic lethality in zebrafish. Testing human FGA variants of uncertain significance in zebrafish identified causative mutations Summary BackgroundMutations in the alpha chain of fibrinogen (FGA), such as deficiencies in other fibrinogen subunits, lead to rare inherited aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 70 publications
4
23
0
Order By: Relevance
“…In contrast to mammals, in which a number of coagulation factors are necessary for embryonic and/or neonatal viability, zebrafish are able to survive the loss of many aspects of the canonical cascade at least until early adulthood. Loss of antithrombin, fibrinogen, FV, and FX are all compatible with development to adulthood 22,[26][27][28]37 . Targeting of f10 in fish results in the absence of larval hemostasis, but is accompanied by extended survival 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to mammals, in which a number of coagulation factors are necessary for embryonic and/or neonatal viability, zebrafish are able to survive the loss of many aspects of the canonical cascade at least until early adulthood. Loss of antithrombin, fibrinogen, FV, and FX are all compatible with development to adulthood 22,[26][27][28]37 . Targeting of f10 in fish results in the absence of larval hemostasis, but is accompanied by extended survival 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic and adult studies have demonstrated the benefits of zebrafish for the study of hemostatic and other human diseases 19,20 . Conservation of coagulation factors in zebrafish is well characterized with a variety of techniques and genetic models [21][22][23][24][25][26][27] . FX knockout (f10 −/− ) zebrafish survive several months into adulthood before succumbing to lethal hemorrhage, suggesting that the model is more resistant to extreme disturbances in hemostasis than mammals 28 .…”
mentioning
confidence: 99%
“…The zebrafish has emerged as a model for thrombosis and hemostasis studies 13 due to the conservation of coagulation proteins 14 and the successful adaptation of in vivo hemostasis tests using transparent zebrafish larvae. [15][16][17][18][19] In addition, targeted mutations in a number of coagulation-related proteins, including fibrinogen, 20,21 have demonstrated the zebrafish's utility in modeling factor deficiencies and for assessing the impact of patient-derived polymorphisms. [22][23][24][25] Zebrafish have nucleated thrombocytes, 26 which are considered cellular equivalents to platelets in hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to mammals, in which a number of coagulation factors are necessary for embryonic and/or neonatal viability, zebrafish are able to survive the loss of many aspects of the canonical cascade at least until early adulthood. Loss of antithrombin, fibrinogen, FV, and FX are all compatible with development to adulthood 22,[26][27][28]45 . Targeting of f10 in fish results in the absence of larval hemostasis, but is accompanied by extended survival 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic and adult studies have demonstrated the benefits of zebrafish for the study of hemostatic and other human diseases 19,20 . Conservation of the coagulation cascade in zebrafish is well characterized with a variety of techniques and genetic models [21][22][23][24][25][26][27] . FX knockout (f10 -/-) in zebrafish demonstrated that the model is more resistant to extreme disturbances in hemostasis than mammals 28 .…”
Section: Introductionmentioning
confidence: 99%